Theoretical description of the ligand function for ionoselective electrodes reversible to metal anion complexes. 2. Selectivity to foreign ions - Egorov, Vladimir V.; Semenov, Andrei V.; Novakovskii, Andrei D.; Akayeu, Yauhen B. (Journal of the Belarusian State University. Chemistry, 2020)
Within the framework of the steady-state diffusion model, the equations have been obtained explicitly describing the selective electrode selectivity coefficient to the ligand ion in relation to foreign ions not forming complexes with zinc ions, as a function of fundamental thermodynamic characteristics (exchange constants of tetrathiocyanatozincate for thiocyanate and foreign ion, concentrations of ion exchanger in the membrane and zinc ion in the sample solution), as well as controllable diffusion parameters (thicknesses of solution and membrane phase diffusion layers, governed by stirring mode and measuring time, respectively). Separate attention is given to cases of measurements in presence and in absence of constant background concentration of zinc ions in the sample solution. It has been shown that selectivity of tetrathiocyanatozincate selective electrode to thiocyanate ion in relation to anions not forming complexes with zinc, is several orders of magnitude higher than selectivity of an ordinary thiocyanate-selective electrode containing higher quaternary ammonium thiocyanate as an ion exchanger, and increases regularly with the background concentration of zinc ions. The results obtained are in general agreement with the experimental data given in the literature. It has been shown that variability of selectivity coefficients caused by variations of diffusion parameters within the limits corresponding to real measuring conditions, can be up to 0.3–0.4 orders of magnitude.